The relation between living group climate, aggression, and callous-unemotional traits in delinquent boys in detention - Heynen, Evelyn (International journal of offender therapy and comparative criminology, 2017)
Aggression and callous-unemotional (CU) traits are common problems in incarcerated delinquent youth. The present study was conducted to examine whether living group climate was associated with aggression and CU traits in late adolescent male offenders (N = 156) in a German youth prison. A structural equation model was fitted to the data and showed associations between repression and reactive aggression and CU traits, but no associations between an open and supportive living group climate and aggression and CU traits. Previous research in Dutch youth prisons did not find a relation between repression and aggression, but a relation between a positive living group climate and less aggression. These different findings may reflect differences in the German and Dutch prison system. Implications for practice are discussed.